Analysis of Supply Chain Wastage for Banana at Wholesale Distribution Points in Tamilnadu - R, Arivazhagan.; P, Geetha. (International Journal of Engineering and Technology, 2018)
India is the second largest producer of overall fruits and vegetables next to China as on 2015. In spite of being a major producer of fruits, various studies were reported that nearly from 20 to 75% of fruits are wasted in India due to various reasons. Fruits wastage was realizing in all stages of its supply chain from farm gate to till it reaches to the consumer. This study concentrates only one supply chain stage i.e. wholesale distribution points in Tamilnadu. This study was conducted based on descriptive research. Scope of this study was confined within Tamilnadu region with 13 specific locations. Data were collected from banana middlemen wholesale traders which include distributors, wholesale agents, commission agents, mandi agents, carry and forward agents, contractors and brokers. Data were collected from 154 wholesale traders through interview as well as survey method by using structured questionnaire. This study revealed that around 6.5% of bananas were getting wasted at wholesale level. This study also identified top three factors which influenced more wastage at wholesale distribution points of banana, they were physical injury, long travel and poor packing method.Â Â